2011
DOI: 10.1016/j.jacc.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Microembolization During Carotid Artery Stenting in Patients With High-Risk, Lipid-Rich Plaque

Abstract: In patients with high-risk, lipid-rich plaque undergoing CAS, MO.MA led to significantly lower microembolization as assessed by using MES counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(46 citation statements)
references
References 31 publications
(30 reference statements)
2
41
1
2
Order By: Relevance
“…Authors showed that deflation of proximal balloon occlusion was associated with higher microembolic signals counting than retrieval of filter devices. In addition to the results of Montorsi et al, 11 the worse results obtained in the flow-reversal group in the present study could be attributed to the larger diameter (9.5 Fr) of the GORE balloon sheath and its higher rigidity than the guiding catheter (7.0 Fr) used in the filter group. The larger size and the high rigidity of the GORE balloon sheath possibly increased shear stress in the artery walls during carotid catheterization, promoting the release of microemboli from plaques.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Authors showed that deflation of proximal balloon occlusion was associated with higher microembolic signals counting than retrieval of filter devices. In addition to the results of Montorsi et al, 11 the worse results obtained in the flow-reversal group in the present study could be attributed to the larger diameter (9.5 Fr) of the GORE balloon sheath and its higher rigidity than the guiding catheter (7.0 Fr) used in the filter group. The larger size and the high rigidity of the GORE balloon sheath possibly increased shear stress in the artery walls during carotid catheterization, promoting the release of microemboli from plaques.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, Montorsi et al 11 monitored all phases of the procedure and found lower incidence of microembolic signals with proximal balloon occlusion than that with filter protection in almost all phases of the procedure, except during the retrieval and deflation of devices. Authors showed that deflation of proximal balloon occlusion was associated with higher microembolic signals counting than retrieval of filter devices.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Only the degree of stenosis has still been employed as the most important inclusion criterion in these studies. However, it is well known that carotid artery stenting may often cause postprocedural lesions on diffusion-weighted MRI and/or ischemic stroke in patients with lipid-rich carotid plaque [45]. Therefore, the presented dual imaging approach may help the clinician to make a decision on therapeutic strategies and options with low morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown proximal protection devices to significantly reduce the perioperative microembolic signal detected by transcranial Doppler, and they also decrease the number of new ischemic lesions when compared to distal protection devices [4,5,6]. Traditionally, patients with a carotid lesion length >10 mm and/or angiographic string sign, a history of prior stroke or coronary artery disease, contralateral carotid stenosis >50%, older age, and female sex were reported to have a higher percentage of adverse outcomes and were also considered high-risk groups [7,8,9].…”
Section: Introductionmentioning
confidence: 99%